Designing solutions to solve Bootstrap entrepreneurship problems. A case study of Tropikana - Loaiza Perez, Daniel Felipe; Ryška, Tomáš, 1976-; Říha, Jan; Vysoká škola ekonomická v Praze. Podnikohospodářská fakulta (2019)
In this thesis, I focus on the use of design thinking and lean tools to solve my needs as a bootstrapped entrepreneur going through an ideation phase. My starting point is an idea for a clothing brand and the millennial demographic. In the thesis, I present secondary research to explain the limitations of a bootstrapped entrepreneur and present the theories of Design Thinking and Lean Start-up, its methodologies, values, philosophies and tools. Then, I use ethnographic fieldwork observations (primary research) as departure point to, through the use of design thinking and lean tools, develop concept, product prototype, test the market and arrive to recommendations towards an iterative market-learning process for the business idea. I finally provide a roadmap for other bootstrapped entrepreneurs like myself that shows how to transform a business idea into a market-test that can lead to a business model or save valuable resources through fast market testing.
Vedoucí práce: Tomáš Ryška
Diplomová práce (Ing.)—Vysoká škola ekonomická v Praze. Fakulta podnikohospodářská, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: international management [obor dipl. práce]; diplomové práce; master's theses